LEADERSHIP STYLE ON DEVELOPMENT POLICY IN SOUTH SUDAN - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to Okumbe (2008), leadership is a process whereby one person influences others to do something on their own volition, neither because it is required nor because of fear of the consequences of noncompliance. This situation shows that leaders play a major role of guiding members to choose to do things freely and decide on their own for the good of community. Sonza (2006), also explains leadership as the ability to lead people and guide their energies towards achieving a goal.” This gives a concept that a leader must fully understand his/her position and roles in any organization. He also states that leadership must be both task and relationship oriented, leaders need an awareness of both the task and relationship and they need to strike a balance between the two. Leader’s power affects both the productivity and freedom of subordinates. If they use less power and authority the groups becomes freer in decision making. When more power and authority are used by leaders, the group lacks freedom in decision making. It is therefore advantageous to the group when leaders balance the power and the freedom of the followers.